The ostracod genus Krithe from the Tertiary and Quaternary of the North Atlantic - Coles, G P; Whatley, R C; Moguilevsky, A (Palaeontology, 1994)
The ostracod genus Krithe is investigated from Cainozoic deep water sediments of the North Atlantic region, mostly from ODP/DSDP cores, although other material is from short cores collected by various NATO vessels, and the geographical and stratigraphical occurrence of the principal species is detailed. The morphological features of the genus are described, and their relative utility in specific discrimination assessed. Of the seventeen species and subspecies described herein, eight have been previously described, five species (Krithe gobanensis, K. regulare, K. minima, K. aquilonia, K. praemorkhoveni) and two subspecies (K. morkhoveni lamellalata, K. morkhoveni ayressi) are new, while two are compared to previously described species. In addition, the stratigraphical ranges and distribution of nineteen nomina nuda species, too rare to be formally described, are tabulated. A new system, based on the nature of the anterior radial pore canals, is used to erect distinct species groups of the genus and as an aid in species determination. The various carapace biocharacters of the genus are reviewed and evaluated with respect to their taxonomic significance; many are shown to be of little use since they are very conservative within Krithe while others, such as size, shape, degree of dimorphism and the nature of the anterior radial pore canals are shown to be of great importance. The stratigraphical ranges of all known Krithe species in the North Atlantic are given and the considerable biostratigraphical significance of the genus is demonstrated. The previous use of Krithe in palaeoenvironmental reconstruction is discussed and the supposed relationship between vestibulum morphology and oxygen level critically evaluated and shown to be wanting, as is the proposition that there is a determinable relationship between the length of species of the genus and water depth